The rise of veterinary forensics. (January 2020) - Parry, Nicola M.A.; Stoll, Alexander
Highlights: Veterinary forensics is an important emerging field. Application of forensics in veterinary cases lags behind its use in medical cases. Educational opportunities will help veterinarians to better manage forensics cases. Interdisciplinary collaborations can improve veterinary forensic investigations. Abstract: Veterinary forensics is rapidly emerging as a distinct branch of veterinary medicine, especially because of increasing mindfulness about animal cruelty, and of the link between acts of cruelty to animals and violence toward humans. Nevertheless, the application of forensic sciences in veterinary cases lags behind its application in medical cases. Although gaps persist in veterinarians' knowledge of forensics and in how to apply this field to medicolegal cases involving animals, continued research and publication in veterinary forensics are rapidly developing the evidence base in this area. Additionally, educational opportunities in veterinary forensics are also increasing at both undergraduate and postgraduate levels. Together, these changes will continue to improve veterinarians' abilities to investigate cases involving animals. To further strengthen these investigations, veterinarians should also collaborate with the appropriate experts in different disciplines of forensic science.